2021
DOI: 10.1097/md.0000000000024590
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Shen-Ling-Bai-Zhu-San combined with chemotherapy for lung cancer

Abstract: Background: Lung cancer (LC), with the high incidence in malignant tumors in the world, and seriously affects people's lives and brings a great economic burden. Previous clinical studies on Shen-Ling-Bai-Zhu-San (SLBZS) combined with chemotherapy for the treatment of lung cancer have been increasing, but there are no systematic reviews. This study aims to systematically study the efficacy and safety of SLBZS combined with chemotherapy in the treatment of LC. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A recent study showed that SBP significantly decreased the serum Th1 in elderly patients with ulcerative colitis complicated by bloody purulent stool ( Li et al, 2021 ). In addition, several clinical studies have demonstrated the safety of SBP in the treatment of patients with irritable bowel syndrome, chronic obstructive pulmonary disease, type 2 diabetes, and lung cancer ( Huang et al, 2019 ; Jiang et al, 2021 ; Mao et al, 2021 ; Shi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that SBP significantly decreased the serum Th1 in elderly patients with ulcerative colitis complicated by bloody purulent stool ( Li et al, 2021 ). In addition, several clinical studies have demonstrated the safety of SBP in the treatment of patients with irritable bowel syndrome, chronic obstructive pulmonary disease, type 2 diabetes, and lung cancer ( Huang et al, 2019 ; Jiang et al, 2021 ; Mao et al, 2021 ; Shi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%